Assessing seasonal forecast use in Western Cape viticulture: a risk framework approach - Khumalo, Fidelity Zwelihle (Department of Environmental and Geographical Science, 2025)
Viticulture refers to the practice of cultivating grapevines for winemaking. With a rapidly changing climate and rising global temperatures, this type of farming is under significant threat. Seasonal forecasts (SF) offer the potential to reduce farmer's vulnerability to climate risks by offering advanced climate information. This study aims to use a risk management framework to identify and compare the level of risk involved in using or not using seasonal forecasts in viticulture. The study's primary data was collected through self-administered semi-structured interviews with viticulturists, agricultural consultants. and farm managers at different wineries within the Western Cape province, South Africa (SA). Wine grape farmers were interviewed to learn about their adaptation strategies in response to climate variability and their use or no-use of SF. The interviews explored the nature and types of risks that exist when climate conditions are above and below normal conditions, with and without the use of SF. A risk management framework, designed for this study's context, was used as a reference point, giving common ground to analysing the responses thematically and produce evidence toward each study objectives. The results show that climate variability poses a significant threat to the yield and quality of wine produced and has a negative impact on the labour and finances in- volved in running a vineyard. Analysing the responses showed that forecast uncertainty is the main driver of low SF uptake thus correlating with a lack of risk precautionary decision-making measures by farmers. Making them more vulnerable to unexpected climate impacts and risks. Farmers who make use of SF are mainly commercial who work with consultants and whose main income is made from selling grapes. The evidence presented suggests that the adoption of a risk framework could potentially aid farmers in making better decisions to help them identify, mitigate and/or avoid risks using SF technology to inform risk identification for present and future climate scenarios of their vine-yards.